Integrasi Pengelolaan Data Akademik Berbasis Web Menggunakan Metode Waterfall pada SMA Tri Dharma Palembang - Amelia Anggraini; Andri Saputra; Muhammad Ridho Ardiansyah (Jurnal Ilmiah Matrik, 2026)
The rapid development of information technology has significantly influenced the education sector, particularly in improving the efficiency and effectiveness of academic data management. SMA Tri Dharma Palembang still relies on conventional tools such as Microsoft Word and Excel for managing academic data, including student records, teacher data, and grades. These manual processes often lead to several issues, such as data redundancy, delays in information delivery, and a higher risk of data loss. This study aims to design and develop a web-based academic information system as a solution to improve data management and accessibility.The system development adopts the waterfall method, which consists of requirement analysis, system design, coding, testing, and maintenance stages. Data collection techniques include observation, interviews, and documentation to obtain accurate information regarding the existing system. The system is designed using Unified Modeling Language (UML), including Use Case Diagrams to represent system functionality, Activity Diagrams to illustrate process flows, and Class Diagrams to define system structure. The result of this study is a web-based academic information system capable of managing student data, teacher data, academic grades, subjects, and generating reports efficiently. The implementation of this system is expected to improve operational efficiency, enhance data accuracy, and provide faster and more reliable access to academic information, thereby supporting better decision-making and improving the overall quality of academic services at SMA Tri Dharma Palembang.